2005
DOI: 10.1111/j.1600-079x.2005.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculatory effects of melatonin in rat skeletal muscle after prolonged ischemia

Abstract: The purpose of this study was to determine microcirculatory effects and response of nitric oxide synthase (NOS) to melatonin in skeletal muscle after prolonged ischemia. A vascular pedicle isolated rat cremaster muscle model was used. Each muscle underwent 4 hr of zero-flow warm ischemia followed by 2 hr of reperfusion. Melatonin (10 mg/kg) or saline as a vehicle was given by intraperitoneal injection at 30 min prior to reperfusion and the same dose was given immediately after reperfusion. After reperfusion, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 64 publications
1
36
1
Order By: Relevance
“…Recent data suggest that oxidative stress is the underlying mechanism of CsA-related apoptosis [1,[14][15][16][17] . Melatonin, the chief indolamine secreted from the pineal gland, is an effective antioxidant agent [2,4,18] . Antioxidant agents operate through neutralizing the toxic reactants, and reducing the molecular damage to the free radicals [2,19] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that oxidative stress is the underlying mechanism of CsA-related apoptosis [1,[14][15][16][17] . Melatonin, the chief indolamine secreted from the pineal gland, is an effective antioxidant agent [2,4,18] . Antioxidant agents operate through neutralizing the toxic reactants, and reducing the molecular damage to the free radicals [2,19] .…”
Section: Discussionmentioning
confidence: 99%
“…Muscle Model [27][28][29][30] Briefly, an incision was made on the ventral aspect of the animal from the anterior iliac spine to the tip of the scrotum. Under observation with a stereomicroscope, the connective tissue of the scrotal sac was removed from around the cremaster muscle by careful blunt dissection.…”
Section: Vascular Pedicle Isolated Cremastermentioning
confidence: 99%
“…Our results showed that eNOS levels decline in MCAO-induced brain injury, and melatonin prevents decrease of eNOS levels. Melatonin provides a significant microvascular protection through the activation of eNOS [23]. Moreover, melatonin-induced protection involves vascular mechanism through the vasodilatation after cerebral ischemia [9].…”
mentioning
confidence: 99%